Determination of the Optimal Biotechnological Parameters for Industrial Production of Protein Hydrolysates for Animal Feed - Marina Belyshkina; Tamara Kobozeva; Mikhail Zagoruiko; Oksana Serebryakova; Maisoon Shaaban; Tatiana Ananeva; Igor Bashmakov (Fermentation)
The main disadvantages of using soybean oil extraction waste as a raw feed material are its high contents of fiber, fat, and anti-nutritional factors. Therefore, several processing methods such as extrusion and hydrolysis are used to overcome these disadvantages and increase the availability of high-quality proteins to animals from this by-product. This study is concerned with the hydrolysis of extruded soybean meal in the presence of bacterial alkaline proteases. The effects of various process parameters were investigated to determine the optimal process parameters for hydrolysis in terms of the total free amino acid and amine nitrogen contents. The experiment included two sets of parameters that were selected for comparison: the temperature and pH in ranges of t 45–50 °C, pH 8–11, compared to the temperature and pH ranges of t = 40–45 °C and pH 7–9, using three enzyme/substrate ratios (1:10, 1:20, and 1:30). The protein hydrolysate was stored for three months after it was treated with two different preservatives (sorbic acid and thymol). Based on the results, it was found that the total free amino acid content was higher when the temperature range was 45–50 °C, the pH range was 8–11, and sorbic acid was used as a preservative.